A comparison of surgical approaches in the treatment of grade C postoperative pancreatic fistula: A retrospective study - Záruba, Pavel; Rousek, Michael; Kočišová, Tereza; Havlová, Karolína; Ryska, Miroslav; Pohnán, Radek (Frontiers in Surgery, 2022)
Background Postoperative pancreatic fistula is one of the most dreaded complications following pancreatic resections with Grade C the most severe. Several possible types of surgical intervention are available but to date, none of them have clearly shown superiority. This study aims to compare different surgical approaches. Methods A retrospective analysis of patients who underwent revision surgery for postoperative pancreatic fistula between 2008 and 2020 was performed. Three surgical approaches were compared: open drainage; a disconnection of the pancreaticojejunostomy; and salvage total pancreatectomy. The data of nine monitored parameters were collected. Selected parameters were statistically analyzed and compared. Results A total of 54 patients were included. Eighteen patients underwent open drainage, 28 had disconnections of the pancreaticojejunostomy and eight had salvage total pancreatectomy. Statistically significant differences were observed in the time of Intensive Care Unit stay, the number of surgical interventions, 90-day mortality, the number of administered blood transfers and treatment costs. Open drainage showed to be superior in each category. The difference in long-term survival also slightly favored simple drainage. Conclusion Open drainage procedure showed to be superior to other types of interventions in most of the monitored parameters. Disconnection of the pancreaticojejunostomy and a salvage total pancreatectomy had similar results, which correlated with the surgical burden of these interventions.